Evaluation of centring date, test-interval and sample-day production methods of computing lactation yield from AM and PM sample-day records* - LIKHI, A K; KHANNA, A S; JAISWAL, U C (The Indian Journal of Animal Sciences, 2013)
The study was conducted on the data pertaining to 646 lactations (commenced over 1969-85) of Holstein-Friesian x Hariana halfbred cattle, maintained in the Department of Animal Breeding, CCS HAU, Hisar, to compare the efficiency of sample-day recording systems for estimating lactation yield. Centring date method resulted in similar error of estimation and higher sampling error in comparison to test-interval and sample-day production methods. The later two methods did not differ significantly. Though the trend remained similar for all the sampling intervals, there was a gradual increase in estimation and sampling error with an increase in sampling interval (30, 40, 50 and 60 days). Among sampling plans, AM - PM and PM - AM (alternate once-a-day sampling with first sample in the evening or morning) gave results closer to twice-a-day (AM + PM) recording. All-AM and All-PM plans lend to significantly over- and under-estimate the lactation yield respectively. Sampling once-aday at shorter intervals (30 or 40 days) estimated the lactation yield with similar results as with twicea-day longer interval sampling.